Clinical spectrum of neuropathy after primary total knee arthroplasty: A series of 54 cases. Issue 6 (4th April 2019) - Speelziek, Scott J.A.; Staff, Nathan P.; Johnson, Rebecca L.; Sierra, Rafael J.; Laughlin, Ruple S.
ABSTRACT: Introduction: Neuropathy after total knee arthroplasty (TKA) can cause significant morbidity but is inconsistently reported. Methods: We reviewed the clinical, electrodiagnostic and perioperative features of all patients who underwent primary TKA at our institution and developed a new neuropathy within 8 weeks postoperatively. Results: Fifty‐four cases were identified (incidence 0.37% [95% confidence interval, 0.28–0.49]) affecting the following nerve(s): peroneal (37), sciatic (11), ulnar (2), tibial (2), sural (1), and lumbosacral plexus (1). In all cases with follow‐up data, motor recovery typically occurred within 1 year and was complete or near‐complete. Conclusions: Post‐TKA neuropathy is uncommon, typically does not require intervention and usually resolves within 1 year. Post‐TKA neuropathy most often affects the nerves surgically at risk. Anesthesia type does not correlate with post‐TKA neuropathy. An inflammatory etiology for post‐TKA neuropathy is rare but should be considered in specific cases. Muscle Nerve 59:679–682, 2019